Effect of Erythropoietin in patients with acute myocardial infarction: five-year results of the REVIVAL-3 trial. Issue 1 (December 2017) - Steppich, Birgit; Groha, Philip; Ibrahim, Tareq; Schunkert, Heribert; Laugwitz, Karl-Ludwig; Hadamitzky, Martin; Kastrati, Adnan; Ott, Ilka
Abstract Background Erythropoietin (EPO) has been suggested to promote cardiac repair after MI. However, the randomized, double-blind, placebo controlled REVIVAL-3 trial showed that short term high dose EPO in timely reperfused myocardium does not improve left ventricular ejection fraction after 6 months. Moreover, the study raised safety concerns due to a trend towards a higher incidence of adverse clinical events as well as a increase in neointima formation after treatment with EPO. The present study therefore aimed to assess the 5-year clinical outcomes. Methods After successful reperfusion 138 patients with STEMI were randomly assigned to receive epoetin beta (3.33×104 U, n  = 68) or placebo (n  = 70) immediately, 24 and 48 h after percutaneous coronary intervention. The primary outcome of the present study- the combined incidence of MACE 5 years after randomization - occurred in 25% of the patients assigned to epoetin beta and 17% of the patients assigned to placebo (RR 1.5; 95% CI 0.8-3.5;p  = 0.26). Target lesion revascularization was required in 15 patients (22.1%) treated with epoetin-ß and 9 patients (12.9%) treated with placebo (p  = 0.15). Analysis of patients in the upper and lower quartile of baseline hemoglobin as an indirect estimate of endogenous erythropoietin levels revealed no significant impact of endogenous erythropoietin on efficiency of exogen administered epoetin-ß in terms of death and MACE. Conclusion These long-term follow-up data show that epoetin beta does not improve clinical outcomes of patients with acute myocardial infarction. Trial registration URLwww.clinicaltrials.gov ; Unique identifier NCT00390832; trial registration date October 19th 2006